Modulation of C5a-C5aR interactions against murine mammary cancer cell line - Kamarudin, N. H.; Bachek, N. F.; Mohd Noor, Mohd Hezmee (Springer, 2021)
Complement C5a is a potent inflammatory chemoattractant and might be a beneficial therapeutic target for the induction of an effective anti-tumour response. C5a agonist and antagonist modulation have been demonstrated to either promote or inhibit tumour development in EMT6 murine mammary cancer cells in both in vitro and in vivo studies. For the in vitro studies Alamar Blue cell viability assay was used for cell viability determination, and an immunofluorescence assay was used to determine the location of C5aR expression on the EMT6 cell line. For the in-vivo experiment, female Balb/c mice were subcutaneously injected with EMT6 tumour cells and subsequently treated with both C5aR agonist and antagonist peptides. At the end of the in vivo study period of 14 days, liver and tumour samples were obtained for an ELISA assay to quantify the levels of TNF-α, caspase, C5a and VEGF-A signals following treatment with both C5aR agonist and antagonist. The in vitro experiment revealed that an expression of C5aR was found on the cell membrane of the EMT6 cells, and treatment with EP54, which is a C5aR agonist, showed low cell viability 48 h posttreatment. For the in vivo experiment, the ELISA assay outcome showed that EP54 significantly promoted higher numbers of circulating signalling proteins except for VEGF-A, suggesting that the C5aR agonist modulation might inhibit tumour growth and also trigger the induction of apoptosis.